Early changes to retinal structure in patients with diabetic retinopathy as determined by ultrawide swept-source optical coherence tomography-angiography - Zeng, Yong; Liu, Miao; Li, Mengyu; Wei, Dinyang; Mao, Mingzhu; Liu, Xinyue; Chen, Sizhu; Liu, Yang; Chen, Bo; Yang, Lei; Liu, Sanmei; Qiao, Lifeng; et al. (Frontiers in Endocrinology, 2023)
Purpose: To investigate the retinal vascular changes of diabetic retinopathy (DR) using the newly developed ultrawide rapid scanning swept-source optical coherence tomography angiography (SS-OCTA) device. Methods: A total of 24 DR patients (47 eyes), 45 diabetes mellitus (DM) patients (87 eyes) without DR, and 36 controls (71 eyes) were enrolled in this cross-sectional and observational study. All subjects underwent 24 × 20 mm SS-OCTA examination. The vascular density (VD) and thickness of the central macula (CM; 1 mm diameter) and temporal fan-shaped areas of 1–3 mm (T3), 3–6 mm (T6), 6–11 mm (T11), 11–16 mm (T16), and 16–21 mm (T21) were compared among groups. The VD and thickness of the superficial vascular complex (SVC) and deep vascular complex (DVC) were analyzed separately. The receiver operating characteristic (ROC) curve was applied to illuminate the prediction value of VD and thickness changes in DM or DR situations. Results: The average VD of the SVC in the CM, T3, T6, T11, T16, and T21 was significantly decreased in the DR group, whereas only T21 showed a significant decrease in the DM group. The average VD of the DVC in the CM and T21 was significantly decreased in the DM group, whereas only the CM showed a significant increase in the DR group. A significant increase in the thickness of SVC nourishing segments was observed in the CM, T3, T6, and T11 in the DR group. In DVC nourishing segments, the thickness of the CM, T3, and T6 increased. No significant changes were observed in the DM group. In the ROC curve, the average VD of the SVC in the CM, T3, and T21 revealed a better DR prediction value (AUC = 0.8608, 0.8505, and 0.8353). In the DVC, only the average VD in the CM revealed a DR prediction value (AUC = 0.8407). Conclusions: The newly developed ultrawide SS-OCTA device revealed much more early peripheral retinal vascular changes than traditional devices. It revealed the retinal vascular changes before clinical manifestation of DR.